Karyotype analysis of Baguio leeks, allium porrum L. (Alliales Alliaceae). - Sorilla, Richie A. (1996.)
Karyotype analysis of C-metaphase chromosomes spreads from mitotic root tip cells of `Baguio leeks,' Allium porrum L. showed a somatic chromosome number of 2n=14. The complement consisted of 4 long and 10 short diploid chromosomes that were further categorized into 3 groups: 2 sm type chromosomes possessing submedian centromeres; 2 st type chromosomes having subterminal centromeres; and 10 m type chromosomes with median centromeres. Mitotic index for the species was noted at 14.58.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Baguio leeks; Allium porrum L